Distributed Intrusion Detection of Byzantine Attacks in Wireless Networks with Random Linear Network Coding - Jen-Yeu Chen; Yi-Ying Tseng (International Journal of Distributed Sensor Networks)
Network coding (NC) can be applied to achieve the maximal information flow in a network. In energy-constraint wireless networks such as wireless sensor networks, applying NC can further reduce the number of wireless transmissions and hence prolong the life time of sensor nodes. Although applying NC in wireless networks is obviously beneficial, it is possible that a malicious node (Byzantine attacker) can take advantage of the inherent vulnerability of error propagation in the NC scheme to corrupt all the information transmissions. In the NC scheme, an intermediate node linearly combines several incoming messages as its outgoing messages. Thus a data error injected in any intermediate nodes will corrupt the information reaching a destination. Recent research efforts have shown that NC can be combined with classical error control codes and cryptography for secure communications or misbehavior detections. Nevertheless, when it comes to Byzantine attacks, these results have limited effects. In this paper, a distributed algorithm is developed to effectively detect, locate, and isolate the Byzantine attackers in a wireless ad hoc network with random linear network coding (RLNC). To the best of our knowledge, our work is the first to address the problem of Byzantine failures in a wireless network with RLNC.